Interactive Learning Strategies as a Means of Increasing Motivation to Learn Sports at the Secondary School Level - Wahyu Kurniadi (Siber Nusantara Review, 2024)
This study aims to determine the influence of interactive learning strategies on students’ motivation to learn physical education at the senior high school level. Using a quantitative research approach with a survey method, data were collected from 100 students through questionnaires distributed at a public high school in Jambi City. The independent variable in this study was the interactive learning strategy, while the dependent variable was learning motivation in physical education. The data were analyzed using descriptive statistics and simple linear regression. The results showed that interactive learning strategies had a significant positive effect on students’ motivation to learn physical education. The coefficient of determination (R²) was 0.422, indicating that 42.2% of the variation in learning motivation could be explained by the application of interactive learning strategies. These strategies, including group discussions, educational games, and the use of varied media, created an engaging and enjoyable learning atmosphere, which enhanced students’ interest, participation, and enthusiasm. This study emphasizes the importance of interactive teaching methods in fostering student motivation and active involvement in physical education learning.